Ecosystem services workshop: reflections: panel discussion #5 - Jessup, David, speaker; Grimmett, Hill, speaker; Knight, Heather, speaker; Knight, Rick, speaker; Goldstein, Josh, speaker; Reid, Robin, speaker; Flynn, Patrick, speaker (Colorado State University. Libraries, 2011)
Workshop participants reflect upon what they learned during the workshop and new questions that arose for them. This discussion began by the ten workshop organizers providing their thoughts.

[Panel discussion #5. Workshop reflections]. Northern Colorado Initiative Panel: What we learned and new questions, David Jessup - Sylvan Dale Ranch, Hill Grimmett - Be Local Northern Colorado, Heather Knight - The Nature Conservancy, Rick Knight - Human Dimensions of Natural Resources, CSU, Josh Goldstein - Human Dimensions of Natural Resources, CSU, Robin Reid - Center for Collaborative Conservation, CSU, Patrick Flynn - Center for Collaborative Conservation, CSU.
Presented at a workshop entitled "Stepping toward the future: marketing environmental services on working lands of the American West" on May 23-25, 2011 on the CSU campus. The purpose of the workshop was to bring together regional and national leaders from the ranching community, conservation organizations, businesses, universities, and government to explore ways to catalyze the development of payments for ecosystem services in Colorado and across the American West. Over 80 participants attended the conference, which also highlighted the CCC's work to create an ecosystem marketplace in northern Colorado.
Includes recorded video presentation.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: ecosystem services